The influence of hormones on inhibiting the processes of skin aging - Trznadel-Budźko, Ewa; Rotsztejn, Helena (Menopause Review/Przegląd Menopauzalny, 2007)
We discuss the influence of hormones on skin aging and draw attention to the menopause.